2023
DOI: 10.7759/cureus.34337
|View full text |Cite
|
Sign up to set email alerts
|

An Extranodal Site of Diffuse Large B-cell Lymphoma Presenting as Ovarian Cancer

Abstract: Due to its uncommon nature, primary ovarian lymphoma has no clinical particularities and can be confused with other ovarian cancers. It poses a twofold diagnostic and therapeutic challenge. An anatomopathological and immunohistochemical study is the crucial step in the diagnosis. Our case was a 55-year-old woman diagnosed with an Ann Arbor stage II E ovarian non-Hodgkin's lymphoma who initially presented with a painful pelvic mass. This case reflects the major role of an immunohistochemical study in the diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The identi ed neoplasms generally exhibited a size exceeding 10 cm, manifesting as either an abdominal mass or an enlarged ovarian. Elevated levels of LDH and CA 125 were frequently observed, aiding in the diagnostic process and subsequent monitoring [10] . Other laboratory parameters and tumor markers generally were normal.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The identi ed neoplasms generally exhibited a size exceeding 10 cm, manifesting as either an abdominal mass or an enlarged ovarian. Elevated levels of LDH and CA 125 were frequently observed, aiding in the diagnostic process and subsequent monitoring [10] . Other laboratory parameters and tumor markers generally were normal.…”
Section: Resultsmentioning
confidence: 99%
“…Until the lack of lymphoid tissue in normal ovaries has contributed to a lack of consensus regarding the tissue origin and pathogenesis of POL [10] . Some researchers hypothesize that chronic in ammatory stimulation of the ovary may play a role in the development of POLs, while others speculate that the lesions may arise from the lymphoid component of teratomas or malignant transformation of primitive reticular cells in the ovarian stroma [6,13] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the lack of typical clinical findings in PFGLT patients, radiological or imaging studies have also been evaluated as useful diagnostic method [ 14 , 22 ]. Previous studies [ 7 , 23 ] showed that the main ultrasonographic manifestations of PLFGT were hypoechoic or extremely hypoechoic solid lesions that were relatively large in size (86.7% is greater than 5 cm), with clear boundaries and regular shapes, and ascites is rare.…”
Section: Discussionmentioning
confidence: 99%
“…Although non-Hodgkin lymphomas may mimic other malignancies, many studies have proven the role of FDG PET/CT in diagnosis [15][16][17][18]. It is difficult to distinguish between ovarian lymphoma and ovarian epithelial malignancies due to the similarity of their clinical manifestations 19. The majority of extranodal lymphomas with ovarian involvement have a younger median age at diagnosis compared with ovarian epithelial malignancies 20,21.…”
mentioning
confidence: 99%